2011
DOI: 10.5194/hess-15-3767-2011
|View full text |Cite
|
Sign up to set email alerts
|

Spatial moments of catchment rainfall: rainfall spatial organisation, basin morphology, and flood response

Abstract: Abstract. This paper describes a set of spatial rainfall statistics (termed "spatial moments of catchment rainfall") quantifying the dependence existing between spatial rainfall organisation, basin morphology and runoff response. These statistics describe the spatial rainfall organisation in terms of concentration and dispersion statistics as a function of the distance measured along the flow routing coordinate. The introduction of these statistics permits derivation of a simple relationship for the quantifica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 55 publications
0
75
1
Order By: Relevance
“…The role of rainfall variability is even greater in climate regimes where a substantial portion of rainfall is convective and runoff is sensitive to this type of rainfall (Morin and Yakir, 2014;Rozalis et al, 2010;Smith et al, 2000;Yakir and Morin, 2011). The hydrological response was found to be sensitive to rainfall spatial variability in very small catchments (less than 1 km 2 ; Bahat et al, 2009), in catchments of few dozen km 2 (Zoccatelli et al, 2011) and larger catchments (> 100 km 2 ; Arnaud et al, 2011). It is therefore essential to use rainfall data with high spatial and temporal resolution Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 98%
“…The role of rainfall variability is even greater in climate regimes where a substantial portion of rainfall is convective and runoff is sensitive to this type of rainfall (Morin and Yakir, 2014;Rozalis et al, 2010;Smith et al, 2000;Yakir and Morin, 2011). The hydrological response was found to be sensitive to rainfall spatial variability in very small catchments (less than 1 km 2 ; Bahat et al, 2009), in catchments of few dozen km 2 (Zoccatelli et al, 2011) and larger catchments (> 100 km 2 ; Arnaud et al, 2011). It is therefore essential to use rainfall data with high spatial and temporal resolution Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 98%
“…The catchment-scale storm velocity has therefore an implicit hydrological meaning. Zoccatelli et al (2011) showed that an upbasin (downbasin) velocity is associated to a decrease (increase) of flood peak with respect to an equivalent stationary storm. A finding which is often reported is that the effect of storm motion on flood peak is maximized when storm velocity has similar magnitude as the channel flow velocity (Singh, 1998;Seo et al, 2012).…”
Section: Ruiz-villanueva Et Al: Extreme Flood Response To Short-dmentioning
confidence: 99%
“…Among these, the direction and the speed of the storm motion with respect to the catchment morphology is probably the most important one (Seo et al, 2012). To examine in a quantitative way these aspects, we use here the concept of "catchment scale storm velocity" proposed by Zoccatelli et al (2011) and based on the spatial moments of catchment rainfall. These statistics, which build on previous work by Viglione et al (2010) and correspond in part to the catchment rainfall statistics reported in Smith et al (2002Smith et al ( , 2005, assess the dependence of the catchment flood response on the space-time interaction between rainfall and the spatial organization of catchment flow pathways.…”
Section: Ruiz-villanueva Et Al: Extreme Flood Response To Short-dmentioning
confidence: 99%
See 2 more Smart Citations